2019
DOI: 10.1097/md.0000000000017213
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of radiologically determined sarcopenia prior to treatment in urologic tumors

Abstract: Objective:Increasing evidence suggests that radiologically determined sarcopenia prior to treatment can serve as a prognostic marker in various tumors. However, there are conflicting conclusions about the prognostic role of sarcopenia in urological tumors. We performed a meta-analysis to assess the association between radiologically determined sarcopenia before treatment and survival outcomes in urological tumors.Methods:A systematically literature search in PubMed, Cochrane databases, and EMBASE was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…The subgroup analyses in our meta-analysis according to cancer type yielded results largely consistent results with previous meta-analyses. Previous literature have identified significant associations in patients with lung cancer [ 10 ], head and neck cancer [ 11 , 18 ], GI cancer [ 9 , 19 , 20 ], liver cancer [ 9 , 21 , 22 ], pancreatic cancer [ 23 ], and urinary tract cancer [ 24 ], with largely consistent effect sized identified in the current meta-analysis. However, other recently published meta-analyses by Zhang et al [ 25 ], Ubachs et al [ 26 ], and Jia et al [ 27 ] have identified a significant association between sarcopenia and survival in breast cancer, ovarian cancer, and hematological malignancies, respectively, contrary to insignificant association identified in the current meta-analysis.…”
Section: Discussionsupporting
confidence: 80%
“…The subgroup analyses in our meta-analysis according to cancer type yielded results largely consistent results with previous meta-analyses. Previous literature have identified significant associations in patients with lung cancer [ 10 ], head and neck cancer [ 11 , 18 ], GI cancer [ 9 , 19 , 20 ], liver cancer [ 9 , 21 , 22 ], pancreatic cancer [ 23 ], and urinary tract cancer [ 24 ], with largely consistent effect sized identified in the current meta-analysis. However, other recently published meta-analyses by Zhang et al [ 25 ], Ubachs et al [ 26 ], and Jia et al [ 27 ] have identified a significant association between sarcopenia and survival in breast cancer, ovarian cancer, and hematological malignancies, respectively, contrary to insignificant association identified in the current meta-analysis.…”
Section: Discussionsupporting
confidence: 80%
“…In patients with gastric cancer, sarcopenia was associated with mortality, postoperative complications, hospital costs, and postoperative hospital stay [ 26 ]. In renal cell carcinoma and urogenital tumors, patients with sarcopenia showed reduced overall survival and cancer-specific survival compared to patients without sarcopenia [ 27 28 ]. Sarcopenia is associated with a reduction in overall and recurrence-free survival in head and neck cancer [ 29 ].…”
Section: Sarcopeniamentioning
confidence: 99%
“…It is generally developed in aged patients or malnourished individuals with risk factors, such as chronic inflammation, oxidative stress, and hormonal changes [12][13][14][15]. Many studies have linked sarcopenia with poor postoperative outcomes in patients with colorectal cancer [16], pancreatic cancer [17], urological cancer [18], and hepatocellular carcinoma [19]. According to a systematic review, the incidence of sarcopenia is as high as 52% in patients with CD when anatomical criteria are considered without functional strength assessment [13,20,21].…”
Section: Introductionmentioning
confidence: 99%